Clinical utility of lymphocyte to C-reactive protein ratio in predicting survival and postoperative complication for esophago-gastric junction cancer. (September 2022) - Tsujiura, Masahiro; Yamamoto, Akira; Imaoka, Hiroki; Shimura, Tadanobu; Kitajima, Takahito; Morimoto, Yuhki; Kawamura, Mikio; Yasuda, Hiromi; Okita, Yoshiki; Yokoe, Takeshi; Okugawa, Yoshinaga; Ohi, Masaki; et al.
Abstract: Background: There are still no useful predictive biomarkers for esophago-gastric junction (EGJ) cancer. We compared 15 candidate inflammation-based markers and investigated the clinical impact of the selected biomarker. Methods: One hundred three patients with EGJ cancer between 2002 and 2020 were enrolled, and associations between clinicopathological data and inflammatory biomarkers were retrospectively analyzed. Area under the curve (AUC) values of 15 candidate biomarkers were compared in receiver operating characteristic (ROC) curves regarding overall survival (OS). Clinical impacts of the selected marker were further investigated regarding long-term prognosis, postoperative complications, and preoperative chemotherapy effects. Results: Lymphocyte/CRP ratio (LCR) demonstrated the highest AUC (0.68552) and was chosen as a candidate biomarker. The high LCR group (LCR >4610) demonstrated significantly better OS (p < 0.0001) and relapse-free survival (RFS) (p < 0.0001) compared with the low LCR group (LCR ≤4610), and preoperative LCR was an independent prognostic factor for both OS (HR 4.97, 95% CI:2.24–11.58; p < 0.0001) and RFS (HR 2.84, 95% CI:1.33–6.14, p = 0.007) in EGJ cancer patients. Another cut-off value was established for postoperative complications, and the incidence rates were significantly higher in the low LCR group (LCR ≤12000) than in the high LCR group (LCR >12000) for all postoperative complications, infectious complications, and surgical site infection (p = 0.013, p = 0.016, and p = 0.030, respectively). Furthermore, patients with decreased LCR after preoperative chemotherapy demonstrated significantly worse RFS compared with patients with increased LCR (p = 0.043). Conclusions: LCR is a potential biomarker to predict long-term prognosis as well as occurrence of postoperative complications in patients with EGJ cancer. Highlights: We compared 15 candidate inflammation-based markers to determine a predictive biomarker in esophago-gastric junction (EGJ) cancer. Lymphocyte/CRP ratio (LCR) demonstrated was chosen as a candidate biomarker after comparative analysis regarding prognosis. LCR was shown as a potential biomarker to predict long-term prognosis and occurrence of postoperative complications in patients with EGJ cancer.